The unconstructable earth : an ecology of separation - Neyrat, Frédéric, 1968- (Book collections on Project MUSE., 2019)
The Space Age is over? Not at all! A new planet has appeared: Earth. In the age of the Anthropocene, the Earth is a post-natural planet that can be remade at will, controlled and managed thanks to the prowess of geoengineering. This new imaginary is also accompanied by a new kind of power, geopower, which takes the entire Earth, in its social, biological and geophysical dimensions, as an object of knowledge, intervention, and governmentality. Far from merely being the fruit of the spirit of geo-capitalism, this new grand narrative has been championed by the theorists of the constructivist turn (be them ecomodernist, postenvironmentalist, or accelerationist to name a few) who have also called into question the great divide between nature and culture.